IoT based smart irrigation, control, and monitoring system for chilli plants using NodeMCU-ESP8266 - Amirul Amin Abd Halim; Roslina Mohamad; Farah Yasmin Abdul Rahman; Harlisya Harun; Nuzli Mohamad Anas (Bulletin of Electrical Engineering and Informatics, 2023)
Traditionally, chilli plant irrigation relies solely on rainwater, which leads to uncontrolled and excessive water consumption and, in turn, unhealthy growth. Furthermore, existing cultivation systems lack systematic control and monitoring to sustain efficient crop growth. Much effort has been put into developing plant irrigation control and monitoring systems in recent decades, resulting in significant technological advancements in the agricultural sector. This paper describes the development of an internet of things-based irrigation control and monitoring system testbed for a chilli plantation. A DHT11 sensor, comprising of moisture, temperature and humidity sensors, were integrated with a node microcontroller NodeMCU ESP8266 unit interacting via wireless fidelity. A controller system that could remotely control the irrigation system was placed in the plantation area. Users interacted with the system through a user interface platform developed using Blynk and Thinger.io. Hence, real-time sensor data were sent to the user interface platform and represented in an easy-to-interpret manner. The results show that the irrigation system testbed can also control the amount of water used, ensuring efficient plant growth.